Prarancangan Pabrik Cumene Dari Benzene dan Propylene Kapasitas 50.000 Ton/Tahun - FACHLIZHA P., Achmad Denanda ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cumene (Isoprpylbenzene) is produced from propylene and benzene. Propylene and benzene form cumene and side product diisopropylbenzene (DIPB) by alkylation process using Î²-zeolite catalyst in fixed bed bubble reactor. The reaction is exothermic and operated adiabatically at 110 0C and 8 atm. Side product DIPB and benzene react and form cumene by transalkylation process using SAPO-5 catalyst in fixed bed reactor. The reaction is exothermic and operated adiabatically at 214.7 0C and 2.3 atm. Both of reactor products are separated in 2 distillation towers. The product is cumene which has a purity 99.1%. Cumene plant is designed with 50,000 tons/year capacity in operating time of 330 days/year. This plant will be built in Cilacap, Central Java with 2 Ha area needed and 212 labours needed. Raw materials needed are propylene 18,308 tons/year, benzene 33,363 tons/year, Î²-zeolite 273,24 kg/year, and SAPO-5 131,14 kg/year. Utilities needed are 943,325 tons/year of water, 550 KW electricity, and 1,710 kL/year of solar. From economic evaluation, we obtain Rp 93,621,899,788 + $ 14,865,471 fixed capital, Rp 311,094,100,046 + $ 516,126 working capital, Rp 1,028,926,971,820 + $ 2,813,356 manufacturing cost, Rp 160,383,184,143 + $ 778,112 general expense, Rp 1,347,032,374,000 sales, Rp 1,189,310,155,963 + $ 3,591,468 total cost. Profit after tax is Rp 61,280,875,064. ROI before tax is 51.25 % and ROI after tax is 25.62 %. POT before tax is 1.63 years and POT after tax is 2.81 years. BEP is 42.93 %, SDP is 29.56 %, and DCFRR is 19.82%. Based on risk analysis, this plant is included in high risk plant and based on economic evaluation, this cumene plant from benzene and propylene is feasible to be assessed further.